Análise do parque urbano do Ingá e suas funcionalidades em Maringá - PR/Brasil - Lisboa, Jonatas Diniz (2021)
In Brazil, mostly, cities that are not contaminated with efficient bodies that manage and maintain systems of public spaces or green areas for leisure and recreation. The creation of urban parks contributes to urban sustainability, with places for sport and leisure, and offers benefits of quality of life in the urban space, also contributing to alleviate possible social tensions, as they provide a space for the approximation of human beings with nature. Keeping ideas in mind, this monograph seeks to understand the role of the Ingá urban park for the city of Maringá-PR, and for its population. For this, an analysis was made of the public equipment that is used on the site, the role of the park in the aesthetic composition of the landscape, as well as its local importance for leisure and sport, and preservation of the environment.